PENGEMBANGAN MODUL FISIKA BERBASIS POTENSI LOKAL “BATIK LUMBUNG DAN TAHU TAMANAN” UNTUK SISWA SMA DI KECAMATAN TAMANAN BONDOWOSO (MATERI SUHU DAN KALOR) - Putri Utami Wulandari Agustin; Sri Wahyuni; Rayendra Wahyu Bachtiar (JURNAL PEMBELAJARAN FISIKA, 2018)
AbstractThe purpose of this research was to develop and described the validity ofPhysics Module Based on Local Potential “Batik Lumbung and Tahu Tamanan” forHigh School Students Tamanan Bondowoso Subdistrict (Material of Temperature andHeat) and described students response toward the module. The design of this researchwas 4D development. The descriptive percentage was used to analyze the modulevalidity. The average of the module from the expert based on didactic, constructionand technical aspect was 94.34%. It was categorized as Very Valid or usable withoutRevision. The average of the module from the user based on format and languageaspect was 93.75%. It was categorized as Very Valid or usable without Revision. Thevalidity of the audience for cognitive aspect was 74.5% and 73.61% for psychomotoraspect. The module was Quite Valid or Usable but Needs to be Revised Small. Basedon the affective aspect, it was categorized as Very Valid or usable without Revisionwith the average score 89.65%. The utilization of the Physics module in learning gotthe positive response from the students with 91.05% in percentage. Physics modulebased on local potential was good and appropriate as the alternative for learningmaterial.Keyword: local potential, module, response, validity